Mrp1 is involved in lipid presentation and iNKT cell activation by Streptococcus pneumoniae. Issue 1 (December 2018) - Chandra, Shilpi; Gray, James; Kiosses, William; Khurana, Archana; Hitomi, Kaori; Crosby, Catherine; Chawla, Ashu; Fu, Zheng; Zhao, Meng; Veerapen, Natacha; Richardson, Stewart; Porcelli, Steven; et al.
Abstract Invariant natural killer T cells (iNKT cells) are activated by lipid antigens presented by CD1d, but the pathway leading to lipid antigen presentation remains incompletely characterized. Here we show a whole-genome siRNA screen to elucidate the CD1d presentation pathway. A majority of gene knockdowns that diminish antigen presentation reduced formation of glycolipid-CD1d complexes on the cell surface, including members of the HOPS and ESCRT complexes, genes affecting cytoskeletal rearrangement, and ABC family transporters. We validated the role in vivo for the multidrug resistance protein 1 (Mrp1) in CD1d antigen presentation. Mrp1 deficiency reduces surface clustering of CD1d, which decreased iNKT cell activation. Infected Mrp1 knockout mice show decreased iNKT cell responses to antigens fromStreptococcus pneumoniae and were associated with increased mortality. Our results highlight the unique cellular events involved in lipid antigen presentation and show how modification of this pathway can lead to lethal infection. The CD1d pathway present lipid antigens resulting in the activation of iNKT cells but the complete pathway remains to be fully elucidated. Here, Chandra et al. use an siRNA screen and identify Mrp1 as crucial for CD1d lipid presentation and activation of iNKT in the context ofStreptococcus pneumoniae infection.